Percepções do ser humano internado em unidade psiquiátrica sobre o viver com doença mental - Ely, Gabriela Zenatti (2015)
The health-disease process involves the perception of every human being and society in a particular time and culture. The objective of the study was to reveal the perception of human being admitted in psychiatric unit about living with mental disease. It is a phenomenological study supported by the theoretical-philosophical framework of Maurice Merleau-Ponty. The field stage was developed in the period January-March 2014, the Inpatient Psychiatric Unit Paulo Guedes at Hospital Universitário de Santa Maria, Rio Grande do Sul, Brazil, after the approval of the Master's Project Protocol by the Ethics Committee Human Research, under nº 26153713.1.0000.5346. The participants were 10 people with aged 21 years to 59 years, hospitalized with mental disease. In the data collection used the phenomenological interview, which was characterized as open and individual. It was opted for the use Paul Ricoeur's hermeneutics, following as interpretation method of speeches. It was proved to three themes from the speeches showing the richness of the existential content that permeates the human lived with mental disease, providing deep reflection: the world of the human beings who experience mental disease; perception of mental disease to humans being who experience the psychiatric hospitalization; and being in the ambiguity of relationship: the freedom of movement. The study unveiled a network of meanings, which was not static, but that opens to numerous interpretations because it is not definitely determined. In addition, health staff, especially nurses, need to gather in their actions the care for human beings who experience the mental disease, in line psychosocial model and principles and guidelines of the National Health System. It aims to promote a network hot singled to care which gift by the host and instigate self-care of the human being through health education; the perspective of completeness actions, promote mental health and the practice of social nursing. Thus, this study may guide the applicability of national mental health politic in perspective to promote the autonomy of the subject by his voice.